The Analysis of Factors of HIV-AIDS Prevention Behavior Street Teenager Bogor City - Azzahroh, Putri; Merka Susanti; Susan Widiastuti (International Journal of Midwifery and Health Sciences, 2024)
Background: Report of the Director General of PP & PL Ministry of Health of the Republic of Indonesia (2012) until June 2012 it was reported that the largest proportion of AIDS sufferers was of productive age, with the most being aged 20-29 years totaling 13,761 cases (47.42%) of that age when viewed from the incubation period is classified into the adolescent age group, while the report from the Bogor city social service, is answered about 24200 the number of people with HIV-AIDS, in the city of Bogor alone there are 210 people with HIV-AIDS, some of them are street children who are registered in the social service city of Bogor. in 2006-2012 there were 6 street teenagers died while in 2012-2018 there were 9 people died due to being infected with HIV-AIDS. Objective: to determine the contribution of the frequency of HI-AIDS prevention behavior based on knowledge, attitudes, peer influence, and the relationship of attitudes, knowledge, and peer influence to the prevention of HIV-AIDS in the streets of Bogor City in 2018 . Methodology: This research design uses analytical methods with a cross sectional approach. The population in this study were all street adolescents who were registered in the Bogor city social service. The research sample was taken using random sampling techniques. Data analysis using univariate and bivariate analysis. Results: The results of this study showed that there was a relationship between knowledge (ρ value = 0.009), and the influence of peers (ρ value = 0.008) on HIV-AIDS prevention behavior in Street teenagers in the city of Bogor in 2019. Conclusions and suggestions: knowledge, attitudes, and influence of peers influence HIV-AIDS prevention behavior in adolescents on the streets of Bogor. It is hoped that adolescents can further enhance their knowledge of HIV-AIDS. Keywords: HIV-ADS prevention behavior, attitude, knowledge, peer influence.